Malignant leydig cell tumor in a 91-year-old man: Case report - Justo,Roberto Mateussi (2019)
ABSTRACT Testicle tumors are a rare entity among men population, accounting for only 1-1.5% of all cancers among men. The stromal tumors of the sexual cord correspond just 4% of all testicular cancers. Only 10% of them are malignant. The major representative of the sex cord-stromal tumors is the Leydig cell tumor, corresponding to 75 to 80% of the total. It has bimodal age incidence, involving children and adults between 30 and 60 years. We report the caso of a 91-year-old man with malignant Leydig cell tumor, presenting increase of the volume of scrotum, local pain and hyperemia. The are few cases in the literature, only 1 with pacient above 85 years old.